Indocyanine green fluorescence imaging technology for the treatment of chylothorax after oesophageal cancer: A case report - Anpeng Ran; Lei Ma; Dan He; Waresijiang Yibulayin; Abulimiti Abulaiti; Zhenhua Wu; Keming Xu; Xiayimaierdan Yibulayin; Paruke Alimu; Xiaohong Sun (Photodiagnosis and Photodynamic Therapy, 2024)
Chylothorax is a serious postoperative complication of oesophageal cancer, and to date, there is no standardized and effective intraoperative diagnostic tool that can be used to identify the thoracic duct and determine the location of lymphatic fistulas. A 50-year-old patient with oesophageal squamous cell carcinoma developed chylothorax after thoracolaparoscopy combined with radical resection of oesophageal cancer. Twelve hours after surgery, 1200 mL of clear fluid was drained from the thoracic drainage tube, and a chyle test was sent. A thoracothoracic duct ligation procedure was performed on the first day after surgery. Although fluid accumulating in the posterior mediastinum was observed, the location of the lymphatic fistula could not be determined. During the surgery, indocyanine green (ICG) was injected into the bilateral inguinal lymph nodes, and a fluorescent lens was used to determine the location of the lymphatic fistula so the surgeon could ligate the thoracic duct. ICG fluorescence imaging technology can help surgeons effectively manage chylothorax after oesophageal cancer surgery. To our knowledge, this is the first report to describe the use of ICG fluorescence imaging technology to treat postoperative chylothorax in patients with oesophageal cancer in China.